Importance of Optimizing Visual Acuity in Vulnerable Seniors Living in an Institution - Chriqui, Estefania; Champoux, Nathalie; Kergoat, Hélène (Canadian Journal of Optometry, 2012)
Visual acuity is an important measurement taken during an eye exam for checking an individual’s ability to see properly and to guide the adjusting of ocular refraction. It is a routine test usually done in a few minutes and with no particularly difficulty. However, this measurement can be more difficult to do in seniors with cognition or communication disabilities. For example, this may be true for a senior with dementia or suffering from aphasia following a stroke. The purpose of this article is to present certain aspects of population aging, data connected with institutionalization of seniors, various conditions that are more prevalent with age, as well as specific factors demonstrating the importance of optimizing vision in seniors. Lastly, this article will provide an overview of various scales available for measuring visual acuity.